Numerical simulations of bulk metal forming process with smooth particle hydrodynamics - Topa, Ameen; Shah, Qasim Hussain (INSI Publications, 2014)
Forging is a complicated bulk metal forming process whereby the material undergoes excessive plastic deformation at elevated temperature. The physical phenomena constituting metal forming processes are difficult to express with quantitative relationships. In this paper, reduced experimental work combined with extensive numerical simulations with LS-Dyna hydrocode is proposed to analyze the forging process. The effects of varying the temperature and punch velocity is investigated. Due the complex nature of the process, standard finite element methods are not capable of simulating this problem. Smooth particle hydrodynamics formulation is adopted as it permits large deformation in the material. The numerical simulations match the experimental results as the final shape and dimensions of the product was successfully achieved. The bulk metal forming process was analyzed with numerical simulations at different temperatures from 650 ~ 800 oC with varying punch velocity from 5 ~ 20 ms-1. The results reveal that the stress levels in the workpiece is inversely proportional to the temperature and directly proportional to the punch velocity.